How Does Rising Rural Population Density Affect Smallholder Agriculture? Milu Muyanga - Muyanga, Milu (2014)
Policy Seminar “Boserup and Beyond Mounting Land Pressures & Development Strategies in Africa” at IFPRI on 4 September 2014. Presentation by Milu Muyanga, Assistant Professor, International Development Agricultural, Food, and Resource Economics, Michigan State University.